Quality Improvement Management in Islamic Senior High Schools (Madrasah Aliyah) - Agissa, Aina Warda; Zainuri, Ahmad; Gani, Muslim (The Future of Education Journal, 2025)
Improving the quality of education is a strategic challenge for Madrasah Aliyah (MA) in facing globalization and increasing educational competition. Educational quality is influenced by various factors such as teacher competence, curriculum, facilities, and institutional management. This study aims to analyze and formulate quality improvement management strategies in MA, with a focus on the role of school principals and the development of effective madrasahs. The research uses a descriptive qualitative approach with a library research method and content analysis of relevant literature. The findings show that implementing quality management through strategic planning, strengthening the role of school leadership, continuous evaluation, and stakeholder involvement is essential in building competitive and high-performing madrasahs. In conclusion, quality improvement in MA requires a structured, collaborative, and long-term approach to produce graduates who are competent, competitive, and morally upright.